Sensing of Water Contaminants: From Traditional to Modern Strategies Based on Nanotechnology - Melo-Freire, R (Elsevier, 2019)
Water is an essential component of life on Earth. This "simple" substance composed of hydrogen and oxygen is mandatory for the survival of human beings. Despite this, the availability of drinking water as well as water sources has been a great concern since the beginning of the 19th century. The number of water contaminants has increased over time, causing enough pollution to restrict the use of the water sources worldwide. Some examples include heavy metals and nanoparticles as inorganic contaminants, and pharmaceuticals and explosives as organic contaminants. Taking this into account, there is an increasing demand for different nanosystems to perform the detection, quantification, and/or identification of water pollutants through simple and cost-effective approaches. For instance, methodologies involving fluorescence, absorbance, and electrochemistry, among others, have already being developed, demonstrating expansive research efforts toward water contaminants sensing. © 2019 Elsevier Inc. All rights reserved..